The dynastic centre and the provinces agents and interactions - Duindam, Jeroen 1962-; Dabringhaus, Sabine 1962- (Rulers & Elites, 2014)
Introduction / Jeroen Duindam -- Part 1. Agents -- The imperial viceroy : reflections on an historical type / Jurgen Osterhammel -- Devolution from the centre to the periphery : an overview of Ottoman provincial administration / I. Metin Kunt -- Broken passage to the summit : Nayancheng's botched mission in the White Lotus War / Yingcong Dai -- Routine promotions : Li Hu and the dusty byways of empire / R. Kent Guy -- Ceremonial demarcations : the viceregal court as space of political communication in the Spanish monarchy (Valencia, Naples, and Mexico, 1621-1635) / Christian Buschges -- The Ambans of Tibet-imperial rule at the Inner Asian periphery / Sabine Dabringhaus -- Part 2. Interactions -- Remonstrating against royal extravagance in imperial China / Patricia Ebrey -- 'True and historical descriptions' : European festivals and the printed record / Helen Watanabe-O'Kelly -- Ceremonial entries and the confirmation of urban privileges in France, c. 1350-1550 / Neil Murphy -- 'Willingly we follow a gentle leader...' : joyous entries into Antwerp / Margit Thofner -- Historical narratives of the Kangxi emperor's inaugural visit to Suzhou, 1684 / Michael G. Chang -- Towards a comparative understanding of rulership : discourses, practices, patterns / Jeroen Duindam